Clinical Trial Drug Safety Assessment for Studies and Submissions Impacted by COVID-19. (1st October 2020) - Nilsson, Mary; Crowe, Brenda; Anglin, Greg; Ball, Greg; Munsaka, Melvin; Shahin, Seta; Wang, Wei
Abstract : Abstract– In this article, we provide guidance on how safety analyses and reporting of clinical trial safety data may need to be modified, given potential impact from the COVID-19 pandemic. Impact could include missed visits, alternative methods for assessments (such as virtual visits), alternative locations for assessments (such as local labs), and study drug interruptions. Starting from the safety analyses typically included in Clinical Study Reports for Phase 2-4 clinical trials and integrated submission documents, we assess what modifications might be needed. If the impact from COVID-19 affects treatment arms equally, analyses of adverse events from controlled data can, to a large extent, remain unchanged. However, interpretation of summaries from uncontrolled data (summaries that include open-label extension data) will require even more caution than usual. Special consideration will be needed for safety topics of interest, especially events expected to have a higher incidence due to a COVID-19 infection or due to quarantine or travel restrictions (e.g., depression). Analyses of laboratory measurements may need to be modified to account for the combination of measurements from local and central laboratories.